Significance of TLC and HPTLC in Phytochemical Screening of Herbal Drugs - Anguraj Moulishankar; Prasanna Ganesan; Madhivanan Elumalai; Karthikeyan Lakshmanan (Journal of Global Pharma Technology, 2021)
Plants provide the most of the pharmacologically active principles like alkaloids, anthraquinones, cardiac glycosides, coumarins, flavonoids, saponins, tannins, essential oils to humans. A large number of the medicinal plants were used by traditional and folk medicinal practitioners for various ailments. The active principles in them are detected by qualitative chemical tests for each category of phytoconstituents. Many chromatographic methods help in separation of the complex mixtures into individual phytoconstituent. Even though Thin Layer Chromatography (TLC) and HPTLC are rapid and easy methods, the selection of stationary phase and solvent system is always a time-consuming process. The general solvent systems for the specific category of secondary metabolites are available in various literatures, but for specific phytoconstituent one should do trial and error method to identify a suitable solvent system. This review article aims to minimize the valuable time of both beginning and experienced researchers by providing well-organized information about TLC and HPTLC in phytochemical screening. Keywords: TLC, HPTLC, Solvent system, Extraction, Phytochemical analysis, Herbal drugs.